BLEEDING RISK FACTORS IN ACUTE CORONARY SYNDROME - Dakić, Sonja; Koraćević, Goran; Perišić, Zoran; Kostić, Tomislav; Apostolović, Svetlana; Šalinger-Martinović, Sonja; Kutlešić-Kurtović, Dušanka; Đorđević-Radojković, Danijela; Božinović, Nenad; Đinđić, Boris; Drašković, Dragana; Maričić, Bojan; et al. (Acta medicae Medianae, 2023)
The modern treatment of patients with acute coronary syndrome (ACS) is justified and effective, but carries a higher risk of bleeding. The study aimed to determine the basic risk factors for bleeding and included 177 patients with ACS who were hospitalized at the Clinic  for Crdiology Niš, in the period from May to September 2013. Based on the presence of bleeding, patients were first divided into patients with bleeding and patients without bleeding. Patients with bleeding were further divided into patients with significant bleeding and patients with less significant bleeding. The study took into account: demographic and anamnestic data, a form of ACS, basic laboratory tests and applied therapy for ACS. In the group of patients with bleeding, there were statistically significantly more non-smokers (χ2 = 6.527, p = 0.038), patients with chronic kidney disease (CKD) (χ2 = 4.192, p = 0.041) and patients with higher CRP values (p = 0.039). In the subgroup of patients with significant bleeding, there were a statistically significantly more frequent patients with CKD (36.4% vs. 6.5%, Fisher's tests: p = 0.007) and higher CRP values (z = 2.452, p = 0.014). In the subgroup of patients with less significant bleeding, the values of hemoglobin (t = 3,496, p = 0,003) were statistically significantly lower compared to other patients. It is interesting to note that the values of hemoglobin, creatinine clearance, and leukocyte count (as a parameter of inflammation) are variables of the PRECISE-DAPT scoring system that appeared in 2017, after our study.
Keywords: acute coronary syndrome, bleeding, risk factors